The Evolutionary Behavior of Shear Strength and Microscopic Mechanisms of Ionic Rare Earths Under Varying Leaching Conditions - Zhongqun Guo; Zhaoming Huang; Qiqi Liu; Haoxuan Wang; Xiaoming Lin (Metals, 2025)
The shear strength properties of ionic rare earth ore bodies are directly related to the stability of mine slopes, which provides important theoretical and engineering support for preventing geological disasters and ensuring the safe extraction of resources. This study investigates the effects of different confining pressures, leaching agent types, and MgSO4 concentrations on the shear strength of ionic rare earth ores through triaxial shear tests. A scanning electron microscopy (SEM) analysis of post-shear mineral samples was conducted to examine the microscopic pore structure, revealing the evolution patterns of the ionic rare earth ore’s microscopic pore structure under various leaching conditions. The results show that the shear strength of the ore body varies significantly under different leaching conditions. After leaching, the shear strength values of the ore body, ranked from highest to lowest, are (NH4)2SO4 > MgSO4 > Al2(SO4)3 > pure water. The (NH4)2SO4 leaching group exhibited an average shear strength approximately 9.8% higher than the pure water group. When comparing the cohesion and internal friction angle of the pure water leaching group, the (NH4)2SO4-leached ore body showed significantly higher cohesion and a smaller internal friction angle. In contrast, the MgSO4 and Al2(SO4)3 leaching groups demonstrated lower cohesion and higher internal friction angles. As the MgSO4 concentration increases, the cohesion of the ore body gradually decreases, the internal friction angle increases, and the shear strength correspondingly increases. Under low-concentration MgSO4 leaching, the number and area of pores in the ore samples initially increase and then decrease, leading to a more complex pore structure. At higher concentrations of MgSO4, the variety of pore shapes increases and becomes more complex, pore randomness decreases, the probability entropy value decreases, and the pore distribution becomes more ordered.